Human Mesenchymal Stromal Cell Sheet Enhances Allograft Repair in a Mouse Model - Xifu Shang; Bing Shu; Yongjun Wang; Zhengliang Luo; Guangxi Wang; Shane Barton; Massimo Max Morandi; Christopher Kevil; Yufeng Dong (Scientific Reports, 2017)
Abstract To determine whether cell sheets generated with long-term passaged (P10) aging human mesenchymal stromal cells (MSCs) could be used for bone tissue regeneration as tissue engineered periosteum in a femoral allograft mouse model similar to fresh passaged (P3) young MSCs. At 3 weeks after transplantation of MSC sheets, results showed more bony callus formed between allograft and host bone ends in both young P3 MSC and aged P10 MSC sheet-wrapped groups when compared to allograft alone. At 6 weeks, while both MSC sheet-wrapped allografts showed more bony callus formation when compared to allograft alone groups, the bony callus size in aged P10 MSC sheet groups was significantly less than young P3 MSC sheet groups. Biomechanical testing confirmed that P3 MSC sheet-grafted femurs had the highest biomechanical strength in the three groups. Histology sections showed that the area of the chondriod callus in the aged P10 MSC sheet groups was significantly larger than in P3 MSC sheet groups. Finally, a significant increase of chondro-osteoclast activity was observed in the P3 MSC sheet-grafted femur. Our data demonstrates that extensive long-term culture-induced MSC aging impaired their osteogenic ability and subsequent bony callus formation, and could be used to induce cartilaginous callus formation.